Environmental Aesthetics 1988
DOI: 10.1017/cbo9780511571213.022
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions in the perception of architecture: identification and interpretation of dimensions of similarity

Abstract: Dimensions in the perception of architecture. I. Identification and interpretation of dimensions of similarity. Scand. J . Psychol. 19, 73-82, 1978.Painvise similarity4issimilarity ratings of 20 slides of buildings representing major architectural styles were subjected to an INDSCAL analysis. Four major similarity dimensions were identified. Subsequently, the stimuli were rated on two batteries of scales: (1) collative and affective ratings, and (2) stylistic and technical ratings. Canonical correlations and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
0
16
0
3
Order By: Relevance
“…Hershberger, 1969). Oostendorp and Berlyne (1978) identified four major dimensions of people's evaluations of 20 buildings representing various architectural styles (from ancient Egyptian to modern): Design clarity, hedonic tone/ arousal, complexity, and familiarity. Nasar (1984) found that responses to urban scenes in Japan and the US were similar in that preferences increased with perceived orderliness, diversity and novelty of the scenes.…”
Section: Empirical Studies Of Aestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hershberger, 1969). Oostendorp and Berlyne (1978) identified four major dimensions of people's evaluations of 20 buildings representing various architectural styles (from ancient Egyptian to modern): Design clarity, hedonic tone/ arousal, complexity, and familiarity. Nasar (1984) found that responses to urban scenes in Japan and the US were similar in that preferences increased with perceived orderliness, diversity and novelty of the scenes.…”
Section: Empirical Studies Of Aestheticsmentioning
confidence: 99%
“…For example, two central factors that emerged in empirical studies of environmental aesthetics are the clarity/ orderliness factor and the richness/diversity/ornateness factor (e.g. Oostendorp and Berlyne, 1978;Nasar, 1984Nasar, , 1988bNasar, , 1999, which correspond to our first and second factors, respectively. Indeed, the two factors reflect two notable aesthetic qualities of landscape design-order and complexity-as distinguished by .…”
Section: Emerged Dimensions and Internal Consistencymentioning
confidence: 99%
“…Lynch'e göre düzenli, okunabilir bir çevre bireyler için somut bir referans sistemi veya bilgi düzenleyicisi olabilmektedir. Çevre psikolojisi alanında farklı araştırmacıların okunabilirlik kavramını açıklamak için düzen ve açıklık (Lynch 1960;Nasar 1994Nasar , 2000Oostendorp ve Berlyne 1978;Deng ve Poole 2012), yol ve yön bulma (Lynch 1960;Weismann 1981;Passini 1988), işaretlendirme/araçlar (Lynch 1960;Newmann 1995Newmann , 2000Doğu ve Erkip 2000) gibi çeşitli boyutları (kavramları) incelediği görülmüştür. Benzer şekilde Köseoğlu (2012), alanyazında okunabilirlik kavramına ilişkin olarak düzen, basitlik, tutarlılık, anlaşılabilirlik ve algılanabilirlik gibi farklı boyutların kullanıldığının görüldüğünü ve tüm bu kavramların, mekânın yapısından doğan özellikleri ifade ettiğini belirtmiştir (Köseoğlu 2012).…”
Section: İlgi̇li̇ çAlişmalarunclassified
“…Açıklık ise bir çevrenin fark edilme süreci ile yakından ilişkili çeşitli unsurların tanımlanabilirliğini yansıtmaktadır (Deng ve Poole 2012). Nasar (1984), Oostendorp ve Berlyne (1978) tarafından tanımlanan açıklık/düzenlilik faktör-lerine benzer şekilde "düzen" boyutu, uygunluk, benzeşim ve açıklık kapsamı/ölçüsü gibi çevrenin organizasyonu ile ilişkilidir. Uyum, uygunluk ve benzeşim kavramları çevredeki harmoniyi geliş-tirebilecek unsurların nasıl bir araya getirildiği ile ilişkili iken okunabilirlik kavramı tüm bu boyutları kapsayacak şekilde, mekânın çeşitli bölümlerinin uyumlu bir örüntü içerisinde organize edilebilmesi ve tanınabilmesidir (Lynch 1960).…”
Section: Düzen Ve Açıklıkunclassified
“…used the same procedure to categorize field and forest environments into three content categories. Oostendorp and Berlyne (1988) used multidimensional scaling techniques developed by Carroll and Chang (1970) to determine common architectural dimensions for conducting pair-wise similarity ratings of buildings.…”
Section: Dimensional Determinationmentioning
confidence: 99%